Mastering R for quantitative finance use R to optimize your trading strategy and build up your own risk management system - Berlinger, Edina (Packt Publishing, 2015)
This book is intended for those who want to learn how to use R's capabilities to build models in quantitative finance at a more advanced level. If you wish to perfectly take up the rhythm of the chapters, you need to be at an intermediate level in quantitative finance and you also need to have a reasonable knowledge of R.
Includes bibliographical references and index. - Online resource; title from cover page (Safari, viewed April 6, 2015)
Keywords: R (Computer program language); Finance -- Computer programs; R (Langage de programmation); BUSINESS & ECONOMICS; Finance; Finance; Computer programs